A Child-centered Method of Interviewing Children with Movement Impairments. (27th May 2018) - Kanagasabai, Parimala S.; Mirfin-Veitch, Brigit; Hale, Leigh A.; Mulligan, Hilda
ABSTRACT: Aims : Children are increasingly included in qualitative research and new methods for interviewing children are emerging. The aim of this article is to describe and discuss the strategies of a child-centered method of data collection for interviewing children with movement impairments to explore their leisure participation experiences. Methods : A study was conducted using an Interpretative Phenomenological Approach (IPA) to explore leisure participation experiences of children with movement impairments aged 6 to 12 years. Various strategies, guided by children, were used to facilitate children's active involvement in the interview process. Results : Twenty-two children (mean age 8.7 years) participated in the interview study, most of them in the presence of their parents or guardian (18 children) and some of them (9 children) with their siblings present. Children enjoyed and were actively engaged in the interview process. Along with talking, 19 children did drawings, 5 children used stickers, 4 children played quiet games, six children shared pictures of their leisure activities, and 16 children physically demonstrated some of their leisure activities, environment, and equipment. Conclusions : A wide range of data collection strategies facilitated children to communicate their leisure participation experiences and to represent children's views without being overly influenced by parental views.